1986
DOI: 10.1111/j.1751-0813.1986.tb02985.x
|View full text |Cite
|
Sign up to set email alerts
|

Caprine retrovirus infection in New South Wales: Virus isolations, clinical and histopathological findings and prevalence of antibody

Abstract: Caprine arthritis-encephalitis virus (CAEV) was isolated by explant cultures of carpal synovial membranes and lung from 7 goats in New South Wales. These goats were clinically affected with the arthritic, neurologic, and pneumonic forms of CAEV infection either singly or in combination. CAEV antibody was detected by the gel immunodiffusion precipitin (GDP) test in 5 of the 7 goats. Serum samples from 2,708 goats, from 115 herds, were examined for CAEV antibody using the GDP test. Approximately one-third of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
4

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
0
11
1
4
Order By: Relevance
“…Economic losses are due to reduced milk yield, mastitis, interaction with bacterial mammary infection, and premature culling [22,23,24,25]. Importantly, both OvLV and CaLV show evidence of breed differences in susceptibility [26,27,28,29,30,31,32,33,34], that together with other evidence [35,36,37,38,39] suggest a host genetic component in susceptibility and control. …”
Section: Small Ruminant Lentiviruses: Background and Existing Intervmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic losses are due to reduced milk yield, mastitis, interaction with bacterial mammary infection, and premature culling [22,23,24,25]. Importantly, both OvLV and CaLV show evidence of breed differences in susceptibility [26,27,28,29,30,31,32,33,34], that together with other evidence [35,36,37,38,39] suggest a host genetic component in susceptibility and control. …”
Section: Small Ruminant Lentiviruses: Background and Existing Intervmentioning
confidence: 99%
“…That is, there need to be multiple genetic versions, known as alleles, to select one or more over others in making breeding decisions. For both sheep and goats, multiple reports support breed differences in seroprevalence of small ruminant lentiviruses as evidence for a genetic basis for probability of infection [26,27,28,29,30,31,32,33,34]. For sheep, a twin study indicated that host genetics played a larger role than viral genetic variability in probability of infection in at least one case [36].…”
Section: Development Of Genetic Marker Tests For Small Ruminant Lementioning
confidence: 99%
See 1 more Smart Citation
“…Seropositive animals were found in 11 of 14 countries investigated. Stud ies were published from Great Britain, Italy and Mexico in 1985 [22][23][24], from Algeria, Australia and Hungary in 1986 [16,25,26] and in 1987 from California, Holland and Spain [27][28][29], Earlier reports came from Denmark [30], Sweden [31], Switzerland [32], France [33], Germany [15] and Israel [34], Since the report from Japan [35] probably deals with CAE, it can be stated that CAE occurs in all continents.…”
Section: Global Distributionmentioning
confidence: 99%
“…CUTLIP et al, 1992;SARAIVA NETO et al, 1995;FERNANDES, 1997;MELO e FRANKE, 1997;RAMALHO, 2000). Todavia, BOHLAND (1998) GREWAL et al, 1986).…”
Section: Lesões Da Artrite-encefalite Dos Caprinosunclassified